Analisis Efektivitas Sensor Termal sebagai Alat Deteksi Keramaian pada Suatu Gedung - Christopher Setiawan Miharjo; Devi Paramita; Grace Natal Liu; Kadek Artika Chintya Meliana; Wesley Aldrich; Lifia Yola Febrianti (Fakultas Teknik Universitas Cenderawasih, 2023)
Crowd has been a normal thing particularly in big cities. This could lead to negative causes such as slower mobilization or social anxiety towards individuals. Ever since the pandemic of Covid-19 lands all over the world, the application of thermal censoring devices has been commonly encountered in public places. The most common use of thermal censors is to detect human body temperature. Therefore, this research is done to analyze the effectivity of thermal cameras on detecting crowd inside a building. By using surveys and literature reviews as our methods, the result of this research shows that from 30 survey respondents, with the average age of 17-25 years old that tends to do indoor activities, 55.6% of them find that crowd is affecting their efficiency during activities. Besides that, 66.7% respondents struggle to measure the crowd level inside a building, also 87.3% of them feels like there should be a solution to this problem. Thus, this research proves that the use of thermal censors on camera for crowd detection is very effective with the accuracy rate of 99%. In conclusion, thermal censor devices are effective to be used as crowd detection devices.